1961
DOI: 10.1210/jcem-21-4-387
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thyroid Function on Carbohydrate Metabolism and a New Method for Assessing Response to Insulin

Abstract: A new method for assessing both glucose utilization and response to insulin is presented. The technique eliminates certain shortcomings of previous methods, which have yielded widely varying results in patients with abnormal thyroid function. The results of the application of the new procedure to 38 euthyroid patients, 15 patients with hyperthyroidism and 13 patients with hypothyroidism, are presented. In the euthyroid group, the mean specific rate constant for glucose utilization (K) was .0349; for the hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

1964
1964
2001
2001

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…treatment was 1-03 ± 0-42, and after treatment 0-89 ± 0-27, (P > 0-05). This indicates that in the hypothyroid state the body is no less efficient in disposing of glucose per unit of insulin than when euthyroid, and does not support the concept of insulin resistance in hypothyroidism reported by Elrick, Hlad & Arai (1961), although two out of the four diabetic curves in our patients reverted to normal with thyroxine therapy. The significantly higher insulin secretion in the first 60 min.…”
contrasting
confidence: 97%
“…treatment was 1-03 ± 0-42, and after treatment 0-89 ± 0-27, (P > 0-05). This indicates that in the hypothyroid state the body is no less efficient in disposing of glucose per unit of insulin than when euthyroid, and does not support the concept of insulin resistance in hypothyroidism reported by Elrick, Hlad & Arai (1961), although two out of the four diabetic curves in our patients reverted to normal with thyroxine therapy. The significantly higher insulin secretion in the first 60 min.…”
contrasting
confidence: 97%
“…Because exogenous insulin increases K values (19), it would be expected that the K value following oral glucose would exceed that following intravenous glucose. However, the increase in insulin concentrations observed in the present studies (2-or 3-fold) was much less than that (10-fold) obtained in the experiments in which 3 units of insulin were administered intravenously (19; Stimmler, L., and H. Elrick, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies with intravenous glucose tolerance tests have revealed an increased glucose utilization in hyperthyroidism and a decreased utilization in hypothyroidism [12,21]; therefore, the abnormalities in oral glucose tolerance tests in hyperthyroidism cited above are probably the expression of the increased rate of glucose absorption from the gut [1]. Increased glucose utilization has also been observed in hyperthyroid rats and in their adipose tissue in vitro [26,23,13]; it has also been postulated for human adipose tissue in hyperthyroidism [6].…”
Section: Insulinspiegel Beimentioning
confidence: 99%